(untitled) (Research, Society and Development, 2021)
The aim of this study was to identify the profile and frequency of infections of the new coronavirus (COVID-19) among healthcare staff at reference hospital for treating the disease. This is a cross-sectional study that used data from COVID-19 Respiratory Syndrome Notification Records and the results obtained by RT-qPCR and Rapid Test. Absolute and relative frequencies were used to describe the sample. For comparisons between positive and negative cases, the chi-square test with Yates continuity correction was deployed, and were considered statistically significant the values that presented p<0,05. A total of 630 professionals were tested, and the highest percentage of confirmed cases was found among female professionals, aged below 40 years, with direct contact with COVID-19 patients, who performed at least one test for SARS-CoV-2; moreover, at the time of testing, headache, sore throat, and myalgia were the most reported symptoms. Eighty-one (81) positive tests were identified. A relationship between symptomology and the number of reagent cases to SARS-CoV-2 was found (p=0.001). Although not significant, it is noteworthy the number of positive cases among female professionals and in those who work in the private clinics. In sum, monitoring and identifying positive SARS-CoV-2 is essential to assist prevention efforts against virus dissemination, as well as to establish safety routines for healthcare professionals.